2012
DOI: 10.1186/1743-0003-9-36
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of robotic exoskeleton training of upper limb reaching movements after stroke

Abstract: This study, conducted in a group of nine chronic patients with right-side hemiparesis after stroke, investigated the effects of a robotic-assisted rehabilitation training with an upper limb robotic exoskeleton for the restoration of motor function in spatial reaching movements. The robotic assisted rehabilitation training was administered for a period of 6 weeks including reaching and spatial antigravity movements. To assess the carry-over of the observed improvements in movement during training into improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 42 publications
2
87
0
1
Order By: Relevance
“…Thus, capturing this objective motor improvement gives insight into the return of UL functioning that was previously lost. Improvements in AROM and PROM were also observed for participants 2 and 3, consistent with previous findings of a positive effect in movement execution and increases in AROM [49] with the addition of RT to stroke rehabilitation. Our data suggest that the magnitude of improvements in AROM and PROM following the TDS-HM intervention may be greatest for people with stroke with the least AROM and PROM at baseline.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, capturing this objective motor improvement gives insight into the return of UL functioning that was previously lost. Improvements in AROM and PROM were also observed for participants 2 and 3, consistent with previous findings of a positive effect in movement execution and increases in AROM [49] with the addition of RT to stroke rehabilitation. Our data suggest that the magnitude of improvements in AROM and PROM following the TDS-HM intervention may be greatest for people with stroke with the least AROM and PROM at baseline.…”
Section: Discussionsupporting
confidence: 90%
“…improve motor function and arm activity of stroke patients, and Frisoli et al (2012) demonstrated that robotic-assisted rehabilitation training including reaching and spatial antigravity movements induced decrement of movement time and improvement of motor recovery and functional movement. Findings from the current study are consistent with previous studies; we believe that the specific and repetitive tasks implemented during robot-assisted reach training led to an improvement of functional movement of the upper extremity in stroke patients.…”
Section: Discussionmentioning
confidence: 94%
“…Inclusion criteria were 1) hemiparesis from a single stroke occurring at least six months prior, 2) sufficient cognition to follow simple instructions and understand the purpose of the study (Mini-Mental State Examination [MMSE] score > 18 points) (Masiero et al 2011), 3) absence of a musculoskeletal condition that could affect the ability to sit safely, and 4) absence of hemispatial neglect. Exclusion criteria were 1) participation in other studies or rehabilitation programs, 2) shoulder subluxation or pain in the upper limbs, or 3) spasticity (Modified Ashworth Scale score > 2) (Frisoli et al 2012). Two of the 12 potential subjects were excluded because they failed to meet the inclusion criteria.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the development of upper-limb [13], hand exoskeleton [14] and wrist [17] [48] rehabilitation robotic system was oriented to stroked patients.…”
Section: Introductionmentioning
confidence: 99%